Current Status of the Indigenous Languages Education Program from the Ministry of Public Education - Karla Ramos Rivas (Universidad Nacional, Costa Rica, 2014)
All of the Costa Rican indigenous languages are in danger of being lost because their spheres of use continue to shrink over time and the intergenerational transmission is diminishing. For this reason, the Costa Rican government has initiated a program to teach indigenous languages as a way to prevent their disappearance. As an effort to obtain a panoramic overview of the current status of indigenous languages education, this article presents a bibliographical review of what has been said about this program, its origins, obstacles and educational achievements. It is concluded that indigenous languages education has not been approached from a second language teaching perspective, there is shortage of educational material and a need for more training and follow-up for teachers, and finally, the non-indigenous population needs to be involved to create a better environment for language revitalization. Aside from providing a formal educational space, little has been done to incorporate indigenous languages in the social life of communities. These languages continue to be anchored in the past and language teachers have been left with a responsibility that should have been shared with the families.